Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) 11-(15+11)=x-(25-9)
=> 11-15-11=x-16
=> -15 = x-16
=>x=1
b) 2-x=17-(-5)
=> 2-x=22
=>x=-20
c) x-12=-9-15
=>x-12=-26
=>x=-14
mik 2k5 nà bạn ^-^
a.11-26=x-16
-15=x-16
x=-15+16=1
b.2-x=22
x=2-22=-20
c.x-12=-24
x=-24+12=-12
a, 11 - ( 15 + 11 ) = x - ( 25 - 9 )
11-15-11=x-25+9
-15=x-16
x=1
b, 2 - x = 17 - ( - 5 )
2-x=22
x=-20
c, x - 12 = ( - 9 ) - 15
x-12=-24
x=-12
d, 9 - 25 = ( 7 - x ) - ( 25 + 7 )
(7-x)-32=-16
7-x=16
x=-9
#H
a)7(x-1)+10=80 b)14-3(x+5)=2 c)65-5(3x-1)=15 d)4(12-3x)-9=3
7(x-1)=80-10 3(x+5)=14-2 5(3x-1)=65-15 4(12-3x)=3+9
7(x-1)=70 3(x+5)=12 5(3x-1)=50 4(12-3x)=12
(x-1)=70:7 (x+5)=12:3 (3x-1)=50:5 (12-3x)=12:4
x-1=10 x+5=4 3x-1=10 12-3x=3
x=10+1 x=4-5 3x=10+1 3x=12-3
x=11 x=(-1) 3x=11 3x=9
x=11:3 x=9:3
x=3,6...7 x=3
a, (-15)+(32.5+80):52
(-15)+(9.5+80):25 = (-15)+(45+80):25 = (-15)+125:25=(-15)+5= -10
b,5.(12-3x)-20=10
5.(12-3x)=10+20 5.(12-3x)=30 12-3x=30:5 12-3x=6 3x=12-6 3x=6 x=6-3 x=3 Vậy x=3
bài 1:
a) 1/3x=-5/3
x=-5
b) x+12/5=37/15
x=1/15
c) x-1/7=-36/7
x=-5
d) 3x-1/2=0
3x=1/2
x=1/6
e) 2/5+x=1/4
x=-3/20
a) x - (11 - x) = -48 + (-12 + x)
x - 11 + x = -48 + (-12) + x
x + x - x = -48 + (-12) + 11
x + 0 = (-60) + 11
x = -49
b) (15 - x) + (x - 12) = 7 - (-8 + x)
15 - x + x - 12 = 7 + 8 + x
15 - x + x - 12 = 15 + x
x + x - x = 15 - 15 + 12
x + 0 = 0 + 12
x = 12
c) (x - 12) - (2x + 31) = -6 - 5
x - 12 - 2x - 31 = -1
x - 12 - 2x = -1 + 31
x - 12 - 2x = 30
x - 2x = 30 + 12
-1x = 42
=> x = -42
d) |x + 5| - (-17) = 20
=> |x + 5| + 17 = 20
=> |x + 5| = 20 - 17
=> |x + 5| = 3
=> \(\orbr{\begin{cases}x+5=3\\x+5=-3\end{cases}}\)
=> \(\orbr{\begin{cases}x=3-5\\x=-3-5\end{cases}}\)
=> \(\orbr{\begin{cases}x=-2\\x=-8\end{cases}}\)
12x2 - 3x = 0
=> 12x2 - 3x = (22 . 3x2) - 3x = 0
=> 3x . (4x - 1) = 0
=> 3x . 4x - 3x . 1 = 0
=> 3x . 4x - 3x = 0
=> 12x - 3x = 0
=> 4x =0
=> x = 0
15 - [ 80 - 12 . ( x + 5 ) ] : 2 = 11
[ 80 - 12 . ( x + 5 ) ] : 2 = 15 - 11 = 4
80 - 12 . ( x + 5 ) = 4 . 2 = 8
12 ( x + 5 ) = 80 - 8 = 72
x + 5 = 72 : 12 = 6
x + 5 = 6
x = 6 - 5 = 1
15-40-6.(x+5)=11
-25-6x-30=11
-6x=11+30+25
-6x=66
x=-11